Pengaruh Total Asset Turnover (TATO), Gross Profit Margin (GPM) Dan Debt To Asset Ratio (DAR) Terhadap Pertumbuhan Laba Pada PT. Adhi Karya (Persero) Tbk - Petrus Keso; Nurul Huda (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research aims to determine and analyze the influence of Total Asset Turnover (TATO), Gross Profit Margin (GPM) and Debt To Asset Ratio (DAR) on Profit Growth at PT. Adhi Karya (Persero) Tbk. This research method uses quantitative methods. The data collection method uses secondary data. The sample technique uses Purposive Sampling. The population in this study is financial report data at PT. Adhi Karya (Persero), Tbk has been listed on the IDX for 17 years, namely from 2004 to 2021, and the sample used is the last 11 years, namely from 2011-2021. Based on the results of this research, it shows that partially the variables Total Asset Turnover (TATO), Gross Profit Margin (GPM) and Debt To Asset Ratio (DAR) have no effect on Profit Growth at PT. Adhi Karya (Persero) Tbk